Socio-economic, governance and health indicators shaping antimicrobial resistance: an ecological analysis of 30 european countries - Andrea Maugeri; Martina Barchitta; Federico Puglisi; Antonella Agodi (Globalization and Health, 2023)
Abstract Background Previous evidence shows that antibiotic use and antimicrobial resistance (AMR) spread are not always perfectly correlated within and between countries. We conducted an ecological analysis to evaluate how demographic, economic, governance, health, and freedom characteristics of 30 European countries contribute to antibiotic consumption and AMR. Methods Using three sources of data (World Bank DataBank, ECDC atlas, and the ESAC-Net database), we created a dataset of: 22 indicators of demographics, health, economic, governance, and freedom; AMR proportions for 25 combinations of pathogens and antibiotics; consumption of antibiotics in the community. We also computed five indexes of demographic, health, economic, governance, and freedom, and an aggregate AMR measure. Relationships between indexes, antibiotic consumption, and AMR proportions were explored using bivariate, multivariable, multivariate, and mediation analyses. Results Multivariate analysis identified three clusters of countries that mainly differed for demographic, health, governance, and freedom indexes. AMR proportion was lower in countries with better indexes (p < 0.001), but not necessarily with lower antibiotic consumption. In multivariable models including all five indexes, an increase in the governance index resulted in significant decreases of overall antibiotic consumption (p < 0.001) and AMR proportion (p = 0.006). Mediation analysis showed that the governance index had an indirect effect on AMR via reducing antibiotic consumption, which accounted only for 31.5% of the total effect. Conclusions These findings could be – at least partially – explained by the contagion theory, for which other factors contribute to high levels of AMR in countries with poor governance. As a result of this evidence, reducing antibiotic use alone is unlikely to solve the AMR problem, and more interventions are needed to increase governance efficiency at global level.